2016
DOI: 10.3390/ijms17060894
|View full text |Cite
|
Sign up to set email alerts
|

Dismantling the Taboo against Vaccines in Pregnancy

Abstract: Vaccinating pregnant women in order to protect them, the fetus, and the child has become universal in no way at all. Prejudice in health professionals add to fears of women and their families. Both these feelings are not supported by even the smallest scientific data. Harmlessness for the mother and the child has been observed for seasonal, pandemic, or quadrivalent influenza, mono, combined polysaccharide or conjugated meningococcal or pneumococcal, tetanus toxoid, acellular pertussis, human papillomavirus, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Despite this evidence, vaccination hesitancy among pregnant women is still high, and stems from a lack of accurate information, probably as a result of the use of unqualified information sources. Indeed, regarding the taboo against vaccines in pregnancy, De Martino affirms that the recommendations of healthcare providers are the keystone of vaccination uptake [ 20 ]. Moreover, a study conducted in 2016 revealed that increasing vaccination coverage against pertussis among pregnant women depends not only on recommendation by physicians, but also on educational interventions and campaigns to promote maternal immunization [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this evidence, vaccination hesitancy among pregnant women is still high, and stems from a lack of accurate information, probably as a result of the use of unqualified information sources. Indeed, regarding the taboo against vaccines in pregnancy, De Martino affirms that the recommendations of healthcare providers are the keystone of vaccination uptake [ 20 ]. Moreover, a study conducted in 2016 revealed that increasing vaccination coverage against pertussis among pregnant women depends not only on recommendation by physicians, but also on educational interventions and campaigns to promote maternal immunization [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, the WHO and an increasing number of health authorities worldwide recommend maternal immunization against influenza, tetanus, and pertussis [36]. Nevertheless, HCPs and pregnant women are still cautious about any intervention including vaccines during pregnancy [106]. The situation has changed in recent years, several new candidate vaccines are specifically being developed for pregnant women, and clinical trials are increasingly being conducted in pregnant women to ensure, before licensure, that vaccine candidates are effective and well tolerated in this population and that these vaccines, once licensed, are indicated for this particular population.…”
Section: Challenges In Vaccinating Special Populationsmentioning
confidence: 99%
“…Indeed, the introduction of vaccination with the vaccinia virus during pregnancy in the late 19th century demonstrated the techniques ability to confer protection in young infants [ 22 ], paving the way for other successful attempts leading to the introduction of antenatal vaccines against pertussis [ 23 ], neonatal tetanus [ 24 , 25 ], influenza virus [ 26 , 27 ] and of the combined tetanus, diphtheria and acellular pertussis (Tdap) vaccine [ 28 , 29 , 30 ]. Despite the increasing prejudices against the pre-birth vaccination practice, a copious amount of data has proven that it is harmless and beneficial [ 31 , 32 , 33 ], so much so that the above mentioned vaccines are currently recommended for use on all expectant mothers ( Table 1 ). Other vaccines, such as those against Hepatitis A and B viruses, Pneumococcus, Meningococcus, Smallpox, Varicella, Rubella and additional live-attenuated vaccines are instead tailored for pregnant women that are subjected to specific risk factors or are indicated only postpartum ( Table 1 ).…”
Section: Maternal Immunizationmentioning
confidence: 99%